Financial and legal regulation of electronic money circulation (Journal of actual problems of jurisprudence, 2022)
This article provides a comprehensive overview of the history of e-money and the current state of the market. Electronic money is regulated by special legislation in the Republic of Kazakhstan. Article gives  proposals and conclusions that contribute to the effective consideration of the problems encountered in practice on various theoretical and practical bases.Easy and fast payment systems that pay for paid services over the Internet are well thought out. It is obvious that electronic payment systems, which are carried out in a simple way, are more flexible for sellers and consumers, as well as Internet users, because they are more flexible. That's why "electronic money" was invented.Plastic cards are an identifiable quick tool that goes into a bank account. However, we cannot classify e-money as a type of plastic card, because: plastic cards have a role only as a means of access to a bank account or as a carrier of electronic money. In essence, plastic cards are not money.Electronic money is a means of payment on a plastic medium used in electronic circuits. This means that money is a means of carrying out payment transactions by transmitting electronic signals without the involvement of paper carriers. The main features of payment systems using electronic money - the equivalent value of money paid in advance by the issuer (issuer - the provider of payment services with the right to issue and reimburse electronic money), stored on card microprocessors, computer hard drives and other devices digitally controlled by its owner. We see that it can be used as a tool without direct participation in banking operations.Keywords: electronic money, payment system, mobile banking, sms-banking, mobile operator payment, electronic wallet, online payment in the Republic of Kazakhstan, electronic money issuer in Kazakhstan, electronic money system.